Minutes (extract)
017a-0080-001 PRIVATE AND CONFIDENTIAL NOT TO BE PUBLISHED N.C.L. 7. 1937 - 1938 Extract MINUTES of a SPECIAL MEETING of the NATIONAL COUNCIL of LABOUR held on Friday, February 4th, 1938. 54. SPAIN: Sir Walter Citrine reported that on behalf of the National Council of Labour he had addressed a communication to the Prime Minister urging that the Government should take steps to prevent the bombing of the civil population in Spain, and that in his reply Mr. Chamberlain had indicated that the matter was to be raised in the House of Commons, and that a statement would be made on that accosion [occasion]. It was reported that Mr. Morgan Jones had raised the matter by Private Member's Motion on Wednesday, February 2nd, when the following Resolution had been accepted by the House "That in the opinion of this House, the growing horror of aerial bombardment of defenceless civilians should be expressed in an international agreement to co-operate in its prohibition, and urges His Majesty's Government to exert its influence to this end." In the course of the Debate the Secretary of State for Foreign Affairs had welcomed the Motion and indicated that the Government had already initiated action on the subject and that a wider survey of the problem by the competent departments of State was also being undertaken prior to representation being made to other Governments concerned. After further discussion, it was Resolved: ''That the action of Sir Walter Citrine be approved and be made the subject of a Press communique." 292/946/17a/80